Biomass, nutrient content, litterfall and nutrient return to the soil in Mediterranean oak forests - Rapp, Maurice; Santa Regina, Ignacio; Rico, Mercedes; Gallego, Humberto Antonio (Forest Ecology and Management, 1999)
We estimated above-ground biomass, nutrient content, litterfall and nutrient return to the soil in deciduous and evergreen Quercus pyrenaica Will., Quercus lanuginosa Lamk and evergreen Quercus ilex L. oak forests, respectively, near Salamanca (Spain) and Montpellier (France). The calculated biomass ranged from 64 to 121 Mg ha ÿ1 . Perennial material (trunks and branches) represented 96±97% in the four Spanish Q. pyrenaica stands and 93% in the French Q. lanuginosa and Q. ilex stands. Q. pyrenaica had higher P, Mg, Fe and Mn contents than the other two species from southern France. In contrast, these latter species had higher N and Ca concentrations. All of these differences were related to soil nutrient availability, especially Ca, Mg, P, Fe and Mn. Comparison of the chemical composition of leaves on trees with that of leaf litter indicated retention and translocation of N, P and K from leaves to perennial biomass and recycling of Ca and Mg from trees to the soil
Keywords: forest biomass; forest ecosystems; litterfall; Q. ilex; Q. lanuginosa; Q. pyrenaica

Biomass, nutrient content, litterfall and nutrient return to the soil in Mediterranean oak forests (Forest Ecology and Management, 1999)
We estimated above-ground biomass, nutrient content, litterfall and nutrient return to the soil in deciduous and evergreen Quercus pyrenaica Will., Quercus lanuginosa Lamk and evergreen Quercus ilex L. oak forests, respectively, near Salamanca (Spain) and Montpellier (France). The calculated biomass ranged from 64 to 121 Mg ha ÿ1 . Perennial material (trunks and branches) represented 96±97% in the four Spanish Q. pyrenaica stands and 93% in the French Q. lanuginosa and Q. ilex stands. Q. pyrenaica had higher P, Mg, Fe and Mn contents than the other two species from southern France. In contrast, these latter species had higher N and Ca concentrations. All of these differences were related to soil nutrient availability, especially Ca, Mg, P, Fe and Mn. Comparison of the chemical composition of leaves on trees with that of leaf litter indicated retention and translocation of N, P and K from leaves to perennial biomass and recycling of Ca and Mg from trees to the soil